2013
DOI: 10.2134/agronj2013.0172
|View full text |Cite
|
Sign up to set email alerts
|

Interspecific Relationships between White Clover, Kentucky Bluegrass, and Canada Thistle during Establishment

Abstract: Forage establishment on fallow fields may be reduced by re-colonization and associated competition from hard to control perennial weeds that reproduce from residual root fragments. We assessed the competitive relationships between regenerating Canada thistle (Cirsium arvense L.) (CT) root fragments and seedlings of white clover (Trifolium repens L.) (WC), and Kentucky bluegrass (Poa pratensis L.) (KBG). Two greenhouse trials were conducted, each comparing 10 combinations of all three species grown in monocultu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 57 publications
0
1
0
Order By: Relevance
“…In our study, all observed legume densities remained below the 80-plant threshold, including the nonsprayed controls, although it is notable that our treatments were intended to assess legume recovery potential from the soil seedbank within a perennial grassland, rather than a newly establishing forage sward on fallow ground. Legume re-establishment within an existing grassland is likely to lead to lower legume densities due to the competitive pressure of grasses, which is known to suppress both white clover [32] and alfalfa [4]. This trend was evidenced here by the decrease in white clover density at the St. Albert location between the summer and fall sampling times, which was attributed to a highly competitive grassland community (largely orchardgrass and meadow brome) at that location, which may have impacted legume seedlings to a greater extent as the growing season progressed.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, all observed legume densities remained below the 80-plant threshold, including the nonsprayed controls, although it is notable that our treatments were intended to assess legume recovery potential from the soil seedbank within a perennial grassland, rather than a newly establishing forage sward on fallow ground. Legume re-establishment within an existing grassland is likely to lead to lower legume densities due to the competitive pressure of grasses, which is known to suppress both white clover [32] and alfalfa [4]. This trend was evidenced here by the decrease in white clover density at the St. Albert location between the summer and fall sampling times, which was attributed to a highly competitive grassland community (largely orchardgrass and meadow brome) at that location, which may have impacted legume seedlings to a greater extent as the growing season progressed.…”
Section: Discussionmentioning
confidence: 99%